Patterns of Rainfall Insurance Participation In Rural India - Giné, Xavier (The World Bank, 2007)
This paper describes the contract design and institutional features of an innovative rainfall insurance policy offered to smallholder farmers in rural India, and presents preliminary evidence on the determinants of insurance participation. Insurance takeup is found to be decreasing in basis risk between insurance payouts and income fluctuations, increasing in household wealth and decreasing in the extent to which credit constraints bind. These results match with predictions of a simple neoclassical model appended with borrowing constraints. Other patterns are less consistent with the "benchmark" model; namely, participation in village networks and measures of familiarity with the insurance vendor are strongly correlated with insurance takeup decisions, and risk-averse households are found to be less, not more, likely to purchase insurance. We suggest that these results reflect household uncertainty about the product itself, given their limited experience with it